IMPLIKASI YURIDIS PUTUSAN PKPU PERUSAHAAN ASURANSI JIWA KRESNA DALAM PUTUSAN NOMOR 389/PDT.SUS-PKPU/2020/PN.NIAGA.JKT.PST - Evelyne Julian Halim; Vera Wheni Setijawati Soemarwi (Jurnal Hukum Adigama, 2022)
Suspension of Payment (PKPU) is a concept in commercial law, which allows a debtor who has goodintentions to submit an application which in essence postpones his obligation to pay his debts. Basedon the provisions of Article 223 juncto Article 2 paragraph 5 of the Law Number 37 of 2004 onBankruptcy and Suspension of Debt Payment (UK-PKPU), an insurance company’s PKPU applicationmay solely filled under the Minister of Finance. However, with the establishment of the FinancialService Authority (OJK), the authority to apply for PKPU of insurance companies has shifted to theauthority of the OJK, as it stated in Law Number 21 of 2011 on OJK. This is also stated in Article 50of Law Number 40 of 2014 on Insurance. However, Verdict of Central Jakarta Commercial CourtNumber 389/Pdt.Sus-PKPU/2020/PN Niaga.Jkt.Pst submitted by the Kresna Life Insurance customerwas granted by the judge, based on the considerations of Article 53 paragraph 2 of the Law Number40 of 2014 on Government Administration, which regulates fictitious approval. Of course, this decisionhas implications for the execution of payments by the Kresna Life Insurance Company as agreed by thecustomers during reconciliation. In addition, this decision has caused legal uncertainty about theinstitution authorized to apply for PKPU against insurance companies. The use of the legal basis bythe judge in granting the decision is a legal error, because UUK-PKPU applies specifically so that thelex specialis derogat legi generali principle applies.